Evaluation of Antioxidant and Organoleptic Properties of Lycopene-Rich Fruits Jelly - Jumaatun, Norasyikin; Zainal Abidin, Munira (Enhanced Knowledge in Sciences and Technology, 2024)
As consumer interest in functional foods rises, lycopene-rich fruit jelly stands out as a flavorful option that aligns with health-conscious lifestyles. This study examined the antioxidant and organoleptic properties of lycopene rich-fruits jelly, which,  25%, 55%, 75% and 100%of papaya and tomato were used to make jelly. A sensory evaluation comprised of 50 participants were done for 8 formulation, 4 formulation for each fruit and each formulation were evaluated for physicochemical proprieties, sensory attributes and antioxidant availability. The moisture content analysis for both papaya and tomato jelly formulations revealed significant differences among the samples. The jelly with 100% of papaya (P100) exhibited the highest moisture content (99.94%), attributed to the presence of papain, an enzyme known to hinder solidification. Similarly, The jelly with 25% of tomato (T25) had the highest moisture content (86.880%) among tomato jelly formulations. The moisture content range in both sets of jelly samples suggests a potential limitation in shelf life, emphasizing the need for refrigeration to prevent microbial spoilage. To combat yeast spoilage, food conditioners and preservatives such as citric acid and potassium metabisulphite were utilized. The pH levels of papaya extract exhibited a gradual decrease from 25% (pH 5.73) to 100% (pH 5.48), whereas tomato extract demonstrated a similar trend with decreasing pH values from 25% (pH 5.26) to 100% (pH 4.87). The total soluble solid content increased progressively in papaya jelly, ranging from 22.69 at 25% concentration to 28.55 at 100% concentration. Similarly, in tomato jelly, the total soluble solid content exhibited a gradual rise from 20.46 at 25% concentration to 24.50 at 100% concentration The texture analysis reveals concentration-dependent trends in stickiness and hardness for papaya and tomato extracts. Papaya demonstrates a significant consistent decrease in stickiness (from -12.92 at 25% to -2.285 at 100%) and hardness (from 33.487 at 25% to 9.415 at 100%). Conversely, tomato stickiness fluctuates, with the lowest at 10.66 at 55%, and an overall increase in hardness (from 29.332 at 25% to 54.04 at 100%). The color analysis of papaya and tomato samples at different concentrations reveals distinct trends. For papaya, as the concentration increases, there is a gradual decrease in lightness (L) and a simultaneous increase in both redness (a*) and yellowness (b*). In Papaya (P25) to (P100), the significant differences are evident in L (p < 0.05), a* (p < 0.05), and b* (p < 0.05). Conversely, for tomatoes, while lightness remains relatively stable, there are significant variations in both a* and b* values, suggesting alterations in the red-yellow spectrum. The sensory evaluation revealed preferences for specific formulations. In tomato jelly, formulation with 25% of tomato (T25) stood out with the highest overall acceptance, while in papaya jelly, 55% papaya concentration (P55) was favored. Antioxidant activity measured through DPPH and ABTS assays demonstrated differences between papaya and tomato jellies, with higher fruit percentages generally correlating with increased antioxidant activity. The total phenolic content (TPC) analysis further supported this, with P100 in papaya jelly showing the highest phenolic content. The 100% concentration tomato jelly (T100) and papaya jelly (P100) exhibited the highest antioxidant content, highlighting their potential health benefits. Conversely, the 25% concentration tomato jelly (T25) and 55% concentration papaya jelly (P55) were favored in sensory evaluation, receiving the highest overall acceptance. This underscores the crucial role of concentration levels in optimizing both the nutritional and sensory qualities of the jellies to meet consumer preferences.